2016
DOI: 10.3762/bjoc.12.52
|View full text |Cite
|
Sign up to set email alerts
|

Regiodefined synthesis of brominated hydroxyanthraquinones related to proisocrinins

Abstract: SummaryDibromobenzoisofuranone 12, synthesized in six steps, was regiospecifically annulated with 5-substituted cyclohexenones 13/36 in the presence of LiOt-Bu to give brominated anthraquinones 14/38 in good yields. Darzens condensation of 30 was shown to give chain-elongated anthraquinone 32. Alkaline hydrolysis of 38 furnished 39 representing desulfoproisocrinin F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In 2016, Mal and co-workers demonstrated a regiodefined synthesis of the brominated hydroxyanthraquinones 47 and 48 , related to proisocrinins (Scheme 3 ). 22 Proisocrinins were the first water-soluble anthraquinone pigments, and two routes have been reported for their synthesis. The first route proceeds through a Darzens condensation, in which the first step is an H–K annulation.…”
Section: Hauser–kraus Annulation In Total Synthesesmentioning
confidence: 99%
“…In 2016, Mal and co-workers demonstrated a regiodefined synthesis of the brominated hydroxyanthraquinones 47 and 48 , related to proisocrinins (Scheme 3 ). 22 Proisocrinins were the first water-soluble anthraquinone pigments, and two routes have been reported for their synthesis. The first route proceeds through a Darzens condensation, in which the first step is an H–K annulation.…”
Section: Hauser–kraus Annulation In Total Synthesesmentioning
confidence: 99%
“…(c) A mixture of 2,4-dibromo-1-hydroxyanthraquinone 3 (1 mmol) and subsequent aryl boronic acid (4,(6)(7)(8)(9)(10)(11)(12) (2.2 mmol), Pd(PPh 3 ) 4 (10 mol %), Bu 4 NBr (1 mmol) and K 2 CO 3 (4 mmol) was stirred in toluene-water mixture (100 and 20 mL) at 100 • C for 4-6 h (TLC) in an argon flow. After cooling to 25 • C, the mixture was diluted with benzene (200 mL) and washed with water.…”
Section: Procedures For Suzuki-miyaura Reactionsmentioning
confidence: 99%
“…A brief literature survey revealed that the routes for the construction of anthraquinone core are primarily based upon five categories, such as Friedel-Crafts condensations of benzene derivatives with functionalized phthalic anhydrides or phthaloyl dichlorides [8], Hauser annulations of cyanophthalides with cyclohexenones [9], Diels-Alder reactions [10,11], cross-coupling reaction and transition metal-mediated reactions [5,12] and biomimetic aldol condensations [13]. However, some annulation processes suffer from serious limitations which include the poorly efficient, and require several synthetic steps, harsh reaction conditions or using of substrates that are synthetically demanding.…”
Section: Introductionmentioning
confidence: 99%